(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
One consequence of Africa’s colonial history appears to be the subjugation of African customs and rites in favour of western values in the legal systems of several African countries. An example of this subjugation is the ‘repugnancy clauses’ that still populate the statute books of several African nations. The effect of the ‘repugnancy clauses’ has been multiplied bytheir suppression of African customs relating to the rearing of children alleged or adjudged to have committed a crime. The article draws upon limited research conducted in 2020 and 2021 in five districts of Zambia on children in conflict with the law as part of a limited study conducted by the author in the preparation of Zambia’s juvenile justice strategy (2021-25).The study collected quantitative data on the rates of children prosecuted in Zambia’s courts for the years 2012-17 and 2019-2020 and determined the rates at which these cases were diverted to customary institutions. It also collected qualitative data in the form of interviews with seven adjudicators, five law enforcement officials and one Chief to make sense of the quantitative data. The research found that although dealing with alleged child delinquents under customary law is a requirement under Zambia’s Juveniles Act, neither law enforcement officials nor magistrates referred cases tocustomary institutions. This article seeks to propose a framework for a balanced incorporation of customary law and its institutions in Zambia’s juvenile justice system. Such framework, the article argues, comports not only with the spirit of the Charter for African Cultural Renaissance, but also the African Charter on the Rights and Welfare of the Child, the UnitedNations Convention on the Rights of the Child, and the Committee on the Rights of the Child’s General Comment 24.